Analysis of the relationship between the meaning of ummī in the hadith of the prophet (PBUH) and the position of worldly knowledge (non-religious knowledge) in Islam - Suleiman, Hassan; Alatas, Alwi; Awang, Abdul Bari (Universiti Teknologi Malaysia, 2025)
In the past, especially during the Abbasid period, worldly knowledge developed rapidly within Islamic civilization. The existence of beneficial worldly knowledge such as medicine, mathematics, astronomy and so on is not contradictory to religious knowledge, but it is complementary to each other, even though religious knowledge holds a higher position. However, in recent times Muslims have been left behind in terms of worldly knowledge, as if this knowledge is foreign to or has no place in religion, while in fact this is not the case. This article discusses the position of worldly knowledge that is beneficial from an Islamic point of view by referring to the main sources of Islam, namely the Qur'an and hadith and also the explanations of scholars. This article uses library research and text analysis methods to explain the relationship between the word ummi in the Prophet's hadith and the position of worldly knowledge (non-religious knowledge) in Islam. This study finds that the illiterate background of the Prophet (PBUH) and the Arab community did not prevent them from learning useful worldly knowledge, and that the presence of the Qur'an in the middle of the Arab community has encouraged the development of not only religious knowledge but also non-religious knowledge in Islamic civilization